Implementasi Media Audio Visual untuk Meningkatkan Kemampuan Menulis Teks Eksplanasi - Suprianto, Edy (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
This research is a class action research. The research aims to reduce problems in class VI-C SDN 004/V Kuala Tungkal, here is the low ability to write explanatory texts. These problems are reduced by implementing audiovisual media. The results showed an increase in the average score of students in the four aspects measured, namely (1) aspects of the content, the average score of students has increased from 18.77 to 26.30; (2) structural aspects, the average score of students has increased from 14.70 to 17.63; (3) vocabulary aspects, the average student score has increased from 12.33 to 16.30; (4) sentence aspects, the average student score has increased from 13.77 to 16.83; and (4) mechanical aspects, the average student score has increased from 7.23 to 8.33. Keywords: audio-visual media, writing, explanatory text.